Basal Pain Sensitivity does not Predict the Outcome of Multidisciplinary Chronic Pain Treatment. Issue 8 (20th March 2015) - Ruscheweyh, Ruth; Dany, Katharina; Marziniak, Martin; Gralow, Ingrid
Abstract: Objectives: Individual differences in underlying, "basal" pain sensitivity are large and have clinical implications. Some studies have suggested that basal pain sensitivity may also predict the outcome of pain treatment. Multidisciplinary chronic pain management programs are effective, but treatment success is individually very different. Therefore, identification of predictors of treatment success is important. This study investigated if basal pain sensitivity predicted the outcome of a 4‐week outpatient multidisciplinary pain management program. Design: Cohort study. Setting: Chronic pain outpatient clinic at the Department of Anesthesiology, Intensive Care Medicine and Pain Therapy of the University of Münster. Methods: Basal pain sensitivity was measured at treatment onset, using comprehensive experimental pain testing (thermal, pressure, and pinprick pain) and the pain sensitivity questionnaire. Primary (clinical pain intensity) and secondary (depression, anxiety, pain‐related disability) outcome parameters were assessed at treatment start, at discharge and 6 months later. Subjects: Sixty five adult chronic pain patients with mixed pain diagnoses. Results: There were significant improvements in clinical pain intensity (from 6.1 ± 2.0 to 5.1 ± 1.8 [0–10]), depression and anxiety at discharge (all P  < 0.001) and of clinical pain intensity (to 5.3 ± 2.3 [0–10]) and pain‐related disability at 6 months (all P  < 0.05). However, treatment outcome was not predicted by any of the basal pain sensitivity measures. Discussion: Results show that basal pain sensitivity is not a reliable predictor of treatment outcome in mixed diagnosis multidisciplinary pain management programs, possibly due to the heterogeneity of patients enrolled in such programs. Clinically useful predictors of treatment success in this setting remain to be identified.